Dynamics of Transformational Leadership and Empowerment on Organizational Citizenship Behavior: Dinamika Kepemimpinan Transformasional dan Pemberdayaan terhadap Perilaku Kewarganegaraan Organisasi - Widi Permadi Ganda Gunawan; Rifdah Abadiyah (Academia Open, 2022)
This study employs a quantitative approach to investigate the relationship between transformational leadership, empowerment, job satisfaction, and organizational citizenship behavior (OCB) in the context of PT Welirang Tirta Mandiri. The research sample consists of 60 respondents, and non-probability sampling is employed. Data analysis is conducted using SmartPLS v.3.0 and the Partial Least Square (PLS) approach. The findings reveal that transformational leadership and empowerment have a significant positive influence on both OCB and job satisfaction. Furthermore, job satisfaction is found to mediate the relationship between transformational leadership and OCB. However, the impact of empowerment on OCB through job satisfaction is insignificant. These results highlight the crucial role of transformational leadership and empowerment in fostering positive organizational behaviors, emphasizing the importance of job satisfaction as a mediator. The implications of these findings provide valuable insights for organizations seeking to enhance employee engagement and cultivate a culture of proactive contributions. Highlights: Transformational leadership and empowerment positively impact organizational citizenship behavior. Job satisfaction mediates the relationship between transformational leadership and organizational citizenship behavior. SmartPLS is used for data analysis in this quantitative study. Keywords: Transformational leadership style, Empowerment, Organizational Citizenship Behavior (OCB), Job satisfaction, SmartPLS